Characterization and prognosis factors of cerebro-vascular disease in Cienfuegos province. - Rubén Bembibre Taboada (Medisur, 2004)
Fundaments: Cerebrovascular disease constitutes the third cause of death and the first cause of severe discapacity in adults in those countries that have a developed health system like ours. Objective: To characterise the patients with cerebrovascular disease and to determine the variables that influence upon their prognosis once it is established. Method: Prospective, descriptive, longitudinal study of a series of cases developed at the University Hospital ¨Dr. Gustavo Aldereguía Lima¨. Questionnaires were applied to the patients that fitted the inclusion criteria (n 1318) Results: The mean age was 66,08 years with a predominance of white patients ( 75,26 %), mainly males ( 56,67%). The risk factor of highest frequency was hypertension ( 43,24 %) The evolution for alive patients without discapacities was 14,71%), alive with discapacities ( 57,96%) and death 27,31%. There was a predominance of ischemic cerebrovascular disease (46,13 % ) of aterothrombotic infarcts and 14,94 % cardioembolic disease. In regards to hemorrhagic disease 13,42 % were intracerebral hemorrhage and 4,55% subarachnoid hemorrhage. There was a prognostic correlation between the clinical variables: consciousness, sight, sensibility, language, tone, Babinski , osteotendious reflexes and muscular force. For the general variables cerebral edema, bacterial bronchopneumonia , displacement of the medial line, diagnosis is some values, CT scan diagnoses in some values for diabetes mellitus and convulsions.